A Randomized Controlled Trial Comparing the McKenzie Method to Motor Control Exercises in People With Chronic Low Back Pain and a Directional Preference - Halliday, Mark H.; Pappas, Evangelos; Hancock, Mark J.; Clare, Helen A.; Pinto, Rafael Z. [UNESP]; Robertson, Gavin; Ferreira, Paulo H. (J O S P T, 2016)
STUDY DESIGN: Randomized clinical trial. BACKGROUND: Motor control exercises are believed to improve coordination of the trunk muscles. It is unclear whether increases in trunk muscle thickness can be facilitated by approaches such as the McKenzie method. Furthermore, it is unclear which approach may have superior clinical outcomes. OBJECTIVES: The primary aim was to compare the effects of the McKenzie method and motor control exercises on trunk muscle recruitment in people with chronic low back pain classified with a directional preference. The secondary aim was to conduct a between-group comparison of outcomes for pain, function, and global perceived effect. METHODS: Seventy people with chronic low back pain who demonstrated a directional preference using the McKenzie assessment were randomized to receive 12 treatments over 8 weeks with the McKenzie method or with motor control approaches. All outcomes were collected at baseline and at 8-week follow-up by blinded assessors. RESULTS: No significant between-group difference was found for trunk muscle thickness of the transversus abdominis (-5.8%; 95% confidence interval [CI]: -15.2%, 3.7%), obliquus internus (-0.7%; 95% CI: -6.6%, 5.2%), and obliquus externus (1.2%; 95% CI: -4.3%, 6.8%). Perceived recovery was slightly superior in the McKenzie group (-0.8; 95% CI: -1.5, -0.1) on a -5 to +5 scale. No significant between-group differences were found for pain or function (P = .99 and P = .26, respectively). CONCLUSION: We found no significant effect of treatment group for trunk muscle thickness. Participants reported a slightly greater sense of perceived recovery with the McKenzie method than with the motor control approach.
Keywords: core stability exercises; Mechanical Diagnosis and Therapy; muscle thickness; transversus abdominis; ultrasound imaging